2022
DOI: 10.3390/cancers14215271
|View full text |Cite
|
Sign up to set email alerts
|

Rosai–Dorfman Disease between Proliferation and Neoplasia

Abstract: Rosai–Dorfman disease (RDD) is a rare myeloproliferative disorder of histiocytes with a broad spectrum of clinical manifestations and peculiar morphologic features (accumulation of histiocytes with emperipolesis). Typically, the patient with RDD shows bilateral painless, massive cervical lymphadenopathy associated with B symptoms. Approximately 43% of patients presented with extranodal involvement. According to the 2016 revised histiocytosis classification, RDD belongs to the R group, including familial and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…The interaction treatment at G 1 B 3 significantly increased leaves chlorophyll content, dry weight percentage, leaves nitrogen, phosphorous, and potassium content which gave 54.24 SPAD, 12.68%, 2.61%, 0.40%, and 3.07%, respectively when compared with the control treatment that showed to have the lowest values of the mentioned traits. Results in Table (3) shown that G 1 treatment improved flowering growth parameters including flowering duration, flower diameter, and flower dry weight percentage that gave 24.78 day, 15.74 cm, and 10.88%, respectively when compared with the control treatment that gave the lowest readings in regard. Nevertheless, B 3 significantly increased the previously mentioned flowering traits and gave 80.06 day, 25.44 day, 16.02 cm, and 11.12% respectively when compared with the control treatment.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The interaction treatment at G 1 B 3 significantly increased leaves chlorophyll content, dry weight percentage, leaves nitrogen, phosphorous, and potassium content which gave 54.24 SPAD, 12.68%, 2.61%, 0.40%, and 3.07%, respectively when compared with the control treatment that showed to have the lowest values of the mentioned traits. Results in Table (3) shown that G 1 treatment improved flowering growth parameters including flowering duration, flower diameter, and flower dry weight percentage that gave 24.78 day, 15.74 cm, and 10.88%, respectively when compared with the control treatment that gave the lowest readings in regard. Nevertheless, B 3 significantly increased the previously mentioned flowering traits and gave 80.06 day, 25.44 day, 16.02 cm, and 11.12% respectively when compared with the control treatment.…”
Section: Methodsmentioning
confidence: 97%
“…Gibberellins stimulate vegetative growth through promoting cell division and elongation along with stimulating some metabolic and IOP Publishing doi:10.1088/1755-1315/1158/4/042007 2 physiological processes. It can also increase enzyme activities resulting in increasing soluble carbohydrates due to enhancing the metabolic activity of both α-amylase and carboxylase and significantly contribute to photosynthates allocation and the production of nucleic acids [3] . Due to the significant importance of ornamental plants in both economy and psychology, considerable researches are conducted to study the response of ornamental plants to plant growth regulators which are considered environmentally safe.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of MAPK pathway genes (NRAS, KRAS, MAP2K1, and, rarely, BRAF) are observed in 20%-30% of cases and point to the neoplastic nature of RDDD. [143][144][145][146][147] RDDD is often a self-limited disease associated with spontaneous regression, although a subset of patients may behave aggressively and require systemic therapies. Patients with organ-or life-threatening diseases might benefit from MEK inhibitors.…”
Section: Alk+ Histiocytosismentioning
confidence: 99%
“…Emperipolesis is characteristically present. Mutations of MAPK pathway genes ( NRAS , KRAS , MAP2K1 , and, rarely, BRAF ) are observed in 20%–30% of cases and point to the neoplastic nature of RDDD 143–147 . RDDD is often a self‐limited disease associated with spontaneous regression, although a subset of patients may behave aggressively and require systemic therapies.…”
Section: Histiocytic and Dendritic Cell Neoplasms (Hdcns)mentioning
confidence: 99%
“…Rosai–Dorfman disease (RDD) is a rare form of non-Langerhans cell histiocytosis (non-LCH) that is characterized by the accumulation of large pale CD68 + , S100 + , and CD1a − histiocytes in various tissues and organs with a spectrum of clinical manifestations [ 1 ]. The incidence rate of RDD is approximately 1:200,000 [ 2 ]. Approximately 43% of patients present with extranodal involvement, and fewer than 5% had neurologic RDD; more than 90% had dura-based mass-mimicking meningiomas, and cerebral parenchyma involvement was sporadic [ 2 ].…”
Section: Introductionmentioning
confidence: 99%